SET-CAN/NUP214 fusion gene in leukemia: general features and clinical advances - Song, Jingyu; Li, Huibo; Fan, Shengjin (Frontiers in Oncology, 2023)
SET-CAN/NUP214 fusion is a recurrent event commonly observed in adult male patients diagnosed with T-cell acute lymphoblastic leukemia (T-ALL) and has occasionally been reported in other diseases such as acute myeloid leukemia (AML), myeloid sarcoma (MS), acute undifferentiated leukemia (AUL), chronic myeloid leukemia (CML) and B-cell acute lymphoblastic leukemia (B-ALL). This fusion gene is derived from chromosome del(9)(q34.11;q34.13) or t(9;9)(q34;q34) and may have an inhibitory effect on primitive progenitor differentiation. The prognosis of the reported patients is varied, with these patients often show resistance to chemotherapy regimens that include high doses of glucocorticoids. The optional treatment has not been determined, more cases need to be accumulated and evaluated. The scope of this review is to summarize the general features and prognostic significance in leukemia associated with the SET-CAN/NUP214 fusion gene and to discuss the methods of detection and treatment, aiming at providing some useful references for relevant researchers in the field of blood tumor.